Symptoms in Blastomycosis, Coccidioidomycosis, and Histoplasmosis Versus Other Respiratory Illnesses in Commercially Insured Adult Outpatients—United States, 2016–2017. (14th October 2020) - Benedict, Kaitlin; Kobayashi, Miwako; Garg, Shikha; Chiller, Tom; Jackson, Brendan R
Abstract: Background: Blastomycosis, coccidioidomycosis, and histoplasmosis cause various symptoms and syndromes, which may present similarly to other infections such as bacterial or viral community-acquired pneumonia, influenza, and tuberculosis. Methods: We used the IBM MarketScan Research Databases to identify adult outpatients with International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM), diagnosis codes during 2016–2017 for blastomycosis, coccidioidomycosis, histoplasmosis, pneumonia (viral, bacterial, Streptococcus pneumoniae, and unspecified pneumonia), influenza; tuberculosis, and other lower and upper respiratory infections. We compared symptoms on and in the 90 days before diagnosis between patients with these diagnosis codes. Results: Fever was less common in blastomycosis (2.6%), histoplasmosis (5.3%), and coccidioidomycosis (9.4%) than in patients with influenza (18.5%) or pneumonia (12.6–16.3%). Fungal diseases resembled bacterial, viral, and unspecified pneumonias for many pulmonary symptoms. However, cough was more common with coccidioidomycosis (31.4%) and less common with histoplasmosis (14.0%) and blastomycosis (13.1%) versus influenza (20.2%). Although less frequent, solitary pulmonary nodule (5.2–14.4%), enlarged lymph nodes (3.7–9.0%), hyperhidrosis (<2%), and erythema nodosum (<2%) were particularly suggestive of fungal diseases. Conclusions: Despite limitations inherent in administrative coding, this analysis of symptom codes across disease types suggests that fungal diseases may be difficult to clinically distinguish from other causes of pneumonia except when certain uncommon symptoms are present. Healthcare providers caring for patients with pneumonia, especially if nonresponsive to conventional treatment, should consider fungal diseases as possible etiologies. Abstract : Health insurance claims data suggest that fungal diseases may be difficult to clinically distinguish from other causes of pneumonia except when certain uncommon symptoms are present. Healthcare providers caring for patients with pneumonia should consider fungal diseases as possible etiologies.